Vascular System: Role of Nitric Oxide in Cardiovascular Diseases - Bian, Ka (J Clin Hypertens (Greenwich), 2008)
In contrast with the short research history of the enzymatic synthesis of nitric oxide (NO), the introduction of nitrate‐containing compounds for medicinal purposes marked its 150th anniversary in 1997. Glyceryl trinitrate (nitroglycerin) is the first compound of this category. On October 12, 1998, the Nobel Assembly awarded the Nobel Prize in Medicine or Physiology to scientists Robert Furchgott, Louis Ignarro, and Ferid Murad for their discoveries concerning NO as a signaling molecule in the cardiovascular system. NO‐mediated signaling is a recognized component in various physiologic processes (eg, smooth muscle relaxation, inhibition of platelet and leukocyte aggregation, attenuation of vascular smooth muscle cell proliferation, neurotransmission, and immune defense), to name only a few. NO has also been implicated in the pathology of many inflammatory diseases, including arthritis, myocarditis, colitis, and nephritis and a large number of pathologic conditions such as amyotrophic lateral sclerosis, cancer, diabetes, and neurodegenerative diseases. Some of these processes (eg, smooth muscle relaxation, platelet aggregation, and neurotransmission) require only a brief production of NO at low nanomolar concentrations and are dependent on the recruitment of cyclic guanosine monophosphate (cGMP)‐dependent signaling. Other processes are associated with direct interaction of NO or reactive nitrogen species derived from it with target proteins and requires a more sustained production of NO at higher concentrations but do not involve the cGMP pathway.